2021
DOI: 10.3389/fonc.2020.593706
|View full text |Cite
|
Sign up to set email alerts
|

Enolase 1 Correlated With Cancer Progression and Immune-Infiltrating in Multiple Cancer Types: A Pan-Cancer Analysis

Abstract: Enolase 1 (ENO1) is an oxidative stress protein expressed in endothelial cells. This study aimed to investigate the correlation of ENO1 with prognosis, tumor stage, and levels of tumor-infiltrating immune cells in multiple cancers. ENO1 expression and its influence on tumor stage and clinical prognosis were analyzed by UCSC Xena browser, Gene Expression Profiling Interactive Analysis (GEPIA), The Cancer Genome Atlas (TCGA), and GTEx Portal. The ENO1 mutation analysis was performed by cBio Portal, and demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
5
12
1
Order By: Relevance
“…There are a substantial number of reports that have demonstrated that human alpha-Eno was responsible for the proliferation and metastasis of a variety of tumors (Fu et al 2015;Sun et al 2019;Xu et al 2020). For example, a study by Gil-Bona et al hypothesized that fungal EVs might also have a possible role in the regulation of intracellular communication as it has been reported for EVs of mammalian cells (Gil-Bona et al 2018).…”
Section: Discussionmentioning
confidence: 97%
“…There are a substantial number of reports that have demonstrated that human alpha-Eno was responsible for the proliferation and metastasis of a variety of tumors (Fu et al 2015;Sun et al 2019;Xu et al 2020). For example, a study by Gil-Bona et al hypothesized that fungal EVs might also have a possible role in the regulation of intracellular communication as it has been reported for EVs of mammalian cells (Gil-Bona et al 2018).…”
Section: Discussionmentioning
confidence: 97%
“…ENO1 overexpression is observed in several cancer types [ 30 , 31 , 32 , 33 ], and is known to be associated with cancer cell stemness [ 34 ]. The inhibition of ENO1 attenuates cell proliferation and induces cell death via glycolytic inhibition [ 16 , 24 ]; however, it is not unlikely that the cytotoxic effect observed is a combined effect of metabolic and non-metabolic functions of ENO1, including plasminogen activation, cell–cell adhesion, and DNA replication [ 35 ]. Moonlighting functions of ALDOA have also been demonstrated in a recent study by Gizak et al A slow-binding inhibitor of ALDOA, UM0112176, induces cell death in cancer cells not via the inhibition of the enzymatic activity but through cytoskeletal disruption and caspase activation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are associated with the Warburg effect, a hallmark of cancer. In addition, some studies have reported that these enzymes are involved in DNA replication and response to DNA damage [ 35 , 36 , 45 ]. Thus, the inhibition of Warburg effects and the TCA cycle and the dysregulation of DNA replication with MSPA treatment could result in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We examined the relation between RELL2 expression levels and six different immune infiltrating levels (macrophages, dendritic cells (DCs), neutrophils, B cells, CD8+ T cells, and CD4+ T cells) using the TIMER database to obtain the score data of the latter, including the gene expression profiles of 32 cancer types [ 18 ]. The estimate R package was used to explore the abundance of immune and stromal components.…”
Section: Methodsmentioning
confidence: 99%